2013
DOI: 10.1126/science.1232139
|View full text |Cite
|
Sign up to set email alerts
|

Vaterite Crystals Contain Two Interspersed Crystal Structures

Abstract: Calcite, aragonite, and vaterite are the three anhydrous polymorphs of calcium carbonate, in order of decreasing thermodynamic stability. Although vaterite is not commonly found in geological settings, it is an important precursor in several carbonate-forming systems and can be found in biological settings. Because of difficulties in obtaining large, pure, single crystals, the crystal structure of vaterite has been elusive for almost a century. Using aberration-corrected high-resolution transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
169
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(182 citation statements)
references
References 29 publications
11
169
1
1
Order By: Relevance
“…For the more soluble phases to precipitate first, their nucleation barriers, and thus surface energies, must be inversely ordered ACC < vaterite < aragonite-calcite. Indeed, molecular dynamics simulations have shown that ACC formation might be barrierless (39), although the nucleation barrier of vaterite is challenging to quantify computationally, due to the complexity of the vaterite structure (44,45). Nevertheless, such inverse relationships between surface energy and bulk metastability would be consistent with other polymorphic oxides (8).…”
Section: Discussionmentioning
confidence: 98%
“…For the more soluble phases to precipitate first, their nucleation barriers, and thus surface energies, must be inversely ordered ACC < vaterite < aragonite-calcite. Indeed, molecular dynamics simulations have shown that ACC formation might be barrierless (39), although the nucleation barrier of vaterite is challenging to quantify computationally, due to the complexity of the vaterite structure (44,45). Nevertheless, such inverse relationships between surface energy and bulk metastability would be consistent with other polymorphic oxides (8).…”
Section: Discussionmentioning
confidence: 98%
“…Although it is necessary to heat to temperature exceeding 730 K for irreversible transformation of vaterite to calcite (Chang et al, 2017), the least stable vaterite can be stabilized in an aqueous solution at ambient conditions preventing its transformation into calcite or aragonite (Trushina et al, 2014). Despite ongoing debate (Kamhi, 1963;Wang and Becker, 2009;Kabalah-Amitai et al, 2013), the formation of vaterite and its transformation mechanisms among the polymorphs can be explained in terms of sequential dissolution and (re)crystallization processes (Figure 2) (Kralj et al, 1997;Spanos and Koutsoukos, 1998;Katsifaras and Spanos, 1999;Wei et al, 2003): (i) initially formed ACC particles transform to the least stable vaterite and (ii) the most soluble vaterite undergoes dissolution and crystallization finally forming the most stable calcite. The solubility of the CaCO3 polymorphs is in decreasing order of ACC, vaterite, aragonite, and calcite (Beck and Andreassen, 2010).…”
Section: Molecular Mechanism and Polymorph Formation Of Cacomentioning
confidence: 99%
“…vaterite can be formed at ambient conditions owing to the kinetic constraints induced by synthesis factors such as temperature and impurities (e.g., Mg) (Ogino et al, 1987;Zhang et al, 2012), which can lead to crystallization of less stable aragonite or the least stable vaterite rather than forming calcite. A number of mechanistic studies have been conducted thus far to reveal the transformation mechanisms among the CaCO3 polymorphs (Kralj et al, 1997;Spanos and Koutsoukos, 1998;Katsifaras and Spanos, 1999;Wei et al, 2003;Rodriguez-Blanco et al, 2011;Zhang et al, 2012;Kabalah-Amitai et al, 2013;Nielsen et al, 2014). Although it is necessary to heat to temperature exceeding 730 K for irreversible transformation of vaterite to calcite (Chang et al, 2017), the least stable vaterite can be stabilized in an aqueous solution at ambient conditions preventing its transformation into calcite or aragonite (Trushina et al, 2014).…”
Section: Molecular Mechanism and Polymorph Formation Of Cacomentioning
confidence: 99%
“…This is due in part to the microcrystalline nature of most synthetic and natural forms which limits the solution methodologies, but moreover, to the similarities between a variety of partially disordered and ordered structural models that can provide seemingly good fits to the diffraction data using x-rays or electrons. Kabalah-Amitai et al 9 concluded that vaterite from sea squirt spicules is actually composed of at least two different crystallographic structures that coexist within a pseudo-single crystal, based on their electron diffraction study. The various structural models proposed for vaterite are based on unit cells indexed from single-crystal x-ray diffraction, powder lab-based and synchrotron x-ray diffraction, and electron diffraction.…”
mentioning
confidence: 99%